Crop performance in complex mixtures: melon and okra in cassava-maize mixture - Ikeorgu, J.; Wahua, T.A.T.; Ezumah, H.C (1984)
We conducted a 2-year investigation at Ibadan, Nigeria, to determine the economic benefits of including melon and okra in a cassava—maize intercropping system. Fresh-root yields of cassava were reduced by 28% by maize in the mixture but only by 3%, 6%, and 9% by okra, melon, or both, respectively. Intercropping had no adverse effect on the grain yield of maize; rather yield was 19% higher in the maize—cassava intercrop than in monoculture. Fresh-fruit yields of okra were reduced by 72%, 89%, and 56% in mixtures with cassava, cassava—maize, and cassava—maize—melon, respectively. Melon-seed yields were decreased by 56% and 76% in mixtures with cassava and cassava—maize, respectively. The cassava—maize cropping system yielded the highest amount of calories per hectare; however, total productivity per unit area of land was highest in the cassava—maize mixture with both okra and melon.